2017
DOI: 10.1093/scan/nsx051
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of emotions varies over time: different regions go with onset- and offset-bound processes underlying emotion intensity

Abstract: According to theories of emotion dynamics, emotions unfold across two phases in which different types of processes come to the fore: emotion onset and emotion offset. Differences in onset-bound processes are reflected by the degree of explosiveness or steepness of the response at onset, and differences in offset-bound processes by the degree of accumulation or intensification of the subsequent response. Whether onset- and offset-bound processes have distinctive neural correlates and, hence, whether the neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 86 publications
6
30
0
Order By: Relevance
“…The first aim is to replicate seminal findings on the neural correlates of emotion explosiveness and accumulation. Consistent with Résibois, Verduyn, and colleagues [ 11 ], we expect explosiveness to be related to activity in the medial prefrontal cortex and accumulation to activity in the posterior insula. The second aim is to replicate the previously found effect of perspective taking on emotion explosiveness and accumulation at the level of self-report.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…The first aim is to replicate seminal findings on the neural correlates of emotion explosiveness and accumulation. Consistent with Résibois, Verduyn, and colleagues [ 11 ], we expect explosiveness to be related to activity in the medial prefrontal cortex and accumulation to activity in the posterior insula. The second aim is to replicate the previously found effect of perspective taking on emotion explosiveness and accumulation at the level of self-report.…”
Section: Introductionsupporting
confidence: 87%
“…These findings are consistent with theoretical claims in the field of emotion dynamics and emotion regulation that emotion onset and offset are partially governed by different processes [ 12 16 ]. However, as the study reported in [ 11 ] was the first attempt to uncover the neural basis of emotion explosiveness and accumulation, it was largely exploratory in nature and its results need to be replicated, which is also in line with recent calls for more replication studies in the field of fMRI [ 17 ].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The psychology and neuroscience of human emotion demonstrate that human affect is time-dependent (e.g. [11]). Accordingly, our approach treats emotions within virtual environments not as momentary responses to evocative stimuli, but as responses that can evolve from anticipation, to reactivity, to recovery and adaptation.…”
Section: High-level: Emotional Responses and Body Image Monitoring Emmentioning
confidence: 99%
“…Nonetheless, to reveal brain regions involved in the processing of affect, the majority of neuroimaging studies have employed static or relatively brief stimuli (e.g., Posner et al, 2009;Baucom et al, 2012;Kim et al, 2017, but see also Raz et al, 2012;2016;Résibois et al, 2017) that may not be adequate to account for the temporal dynamics of the experience (Waugh and Schirillo, 2012). The use of movies in the functional magnetic resonance imaging (fMRI) setting could provide valuable insights instead.…”
Section: Introductionmentioning
confidence: 99%